Photoprotection in adolescents: what they know and how they behave - Andreola, Gabriel Martinez (An Bras Dermatol, 2018)
BACKGROUND: The greatest sun exposure occurs until adolescence and this is the only factor involved in photocarcinogenesis subject to modification with photoprotection. OBJECTIVE: The objective of this study was to evaluate the habits and knowledge of adolescents regarding photoprotection. METHOD: Cross-sectional study that included 512 students from primary and high school. Data were collected by questionnaires with questions about habits and knowledge on sun protection. For data analysis, Pearson's Chi-square test and Yates test were applied, with 5% level of significance. RESULTS: We evaluated 512 students, with a mean age of 14 years old. The teenagers agreed that ultraviolet rays cause skin cancer and aging (96% and 70%, respectively). Knowledge about the occurrence of burns even on cloudy days was recorded in 68% of cases, as well as the need for photoprotection for sports in 72%. The source of information about sun protection were by parents in 55%. In 70% was observed previous occurrence of sunburn, the daily use of sunscreens was found in 15% and 67% used only at the beach. of sunscreens with SPF higher than 30 was reported by 70% of students and 57% reported going to the beach between 10h and 16h. In 68% of cases it was registered insufficient sun protection, attributed, in 57% of the time to forgetfulness. STUDY LIMITATIONS: The sample refers to two schools of Curitiba (PR), Brazil. CONCLUSION: Teenagers know the risks of sun exposure, but they do not adopt the practices for adequate protection.